Produktivitas Penulis Indonesia di Riset Energi Internasional (Kajian Jurnal ScienceDirect) - Himawanto, Himawanto (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
National energy crisis is the biggest challenge that needs to be addressed through research activities in order to produce innovative technologies. While research products that have created will affect to the growth of scientific publications. ScienceDirect is one of reputable source of knowledge that also accommodates the national of energy research products. So its was revealed interesting in order measure the progress of science in Indonesia. Bibliometric evaluations used to determine product research capacity, scientists membership, and national territory champions. During 2006-2015 the performance of national scientists in international energy research collected in 18 scientific journals with of 322 articles results. Indonesia has the highest achievement through performance of scientists that majority affiliated with academic and government. Besides contributing independently, scientists also produces research work collaboratively reached 91.19%. The number of collaborative greatly affect to the national capability and demonstrates the expertise of Indonesia in leading of energy research cooperation. Moreover, there are many countries in four continents have participated and affect to the image of Indonesia in global arena. There are five island areas nationwide based on geographical expansion of institutions and researchers on the island of Java has participate significantly.